Meeting at new Oddfellows home in Saratoga - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Gathering at the new Odd Fellows home in Saratoga. This gathering may have been "Opinion day" for members of the I.O.O.F. Members of the fraternity wearing regalia can be found standing on a stage on the far right of the photograph. Other members are scattered throughout the photorgraph, some distinguishing themselves with large feather plume hats.